Ontology Based RT-Delphi with Explanation Capabilities - Ahmed Omran; Motaz Khorshid (IAES International Journal of Artificial Intelligence (IJ-AI), 2014)
Real-Time (RT) Delphi approach is widely used method for knowledge acquisition process. The current RT-Delphi approach ignores considering the unifying domain concepts and their attributes. This limitation can provide the contradiction of the domain experts' judgments and increasing misunderstandings when talking about specific topics. In addition, the current RT-Delphi ignores the explanation capabilities for consensus results, which it is vital for policy/decision makers to be more confidence. The core of this research is to develop ontology-based RT-Delphi with explanation capabilities. We applied the developed approach in to two crucial important case studies in Egypt, which are food security and water security.